INFORMATIONAL AND COMMUNICATIVE COMPETENCE FORMATION IN THE TEXT ACTIVITY PROCESS - A. A. Melikhova (Russian State Vocational Pedagogical University, 2015)
The paper is devoted to the problem of fostering the informational and communicative competence, regarded as the capability of meaningful work with information, its personalized understanding and implementation in professional activity. As a solution to the problem, the author indicates the developing potential of text activity, performed in a dialog enriched by ideas of hermeneutics and meaning-making. The competence in question should be developed stage-by-stage by role-playing the professionally focused situations; applying the symbolic contextual approach by A. A. Verbitsky; using different tasks to enable understanding, comprehension of new semantics, correlation with students' personal experience; and promoting self-understanding, selfawareness and value attitude. The above activities  should result in training competent experts with a broad cultural outlook and capability to adapt to and work in the modern information society, find creative solutions to the complex challenges, and communicate in the global cross-cultural environment.